2008
DOI: 10.1002/app.27752
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of carbon fillers on tensile and flexural properties in liquid‐crystal polymer based resins

Abstract: One emerging market for thermally and electrically conductive resins is bipolar plates for use in fuel cells. Adding carbon fillers to thermoplastic resins increases the composite thermal and electrical conductivity. These fillers have an effect on the composite tensile and flexural properties, which are also important for bipolar plates. In this study, various amounts of three different types of carbon (carbon black, synthetic graphite particles, and carbon fibers) were added to Vectra A950RX liquidcrystal po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Because prior tensile and flexural strength tests were performed using carbon black and synthetic graphite in a Vectra liquid crystal polymer matrix (LCP) for use in fuel cell bipolar plate applications,35 a comparison is made in Figures 6 and 7. The filler volume fractions used in the LCP matrix are summarized in Table VIII 35.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because prior tensile and flexural strength tests were performed using carbon black and synthetic graphite in a Vectra liquid crystal polymer matrix (LCP) for use in fuel cell bipolar plate applications,35 a comparison is made in Figures 6 and 7. The filler volume fractions used in the LCP matrix are summarized in Table VIII 35.…”
Section: Resultsmentioning
confidence: 99%
“…Because prior tensile and flexural strength tests were performed using carbon black and synthetic graphite in a Vectra liquid crystal polymer matrix (LCP) for use in fuel cell bipolar plate applications,35 a comparison is made in Figures 6 and 7. The filler volume fractions used in the LCP matrix are summarized in Table VIII 35. The tensile modulus increased as a function of the filler volume percent with increasing filler concentration for both carbon black and synthetic graphite in the polypropylene, as indicated in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhou et al [16] used Al 2 O 3 with different size to fill silicone rubber, and reported that nanosized Al 2 O 3 composite exhibited higher thermal conductivity and mechanical properties than the micro-sized one. The influence of hybrid fillers was also investigated [17,18]. However, reports on how to enhance the thermal conductivity and mechanical properties of the polymer composites simultaneously are still quite limited.…”
Section: F S Wangmentioning
confidence: 99%